Design of an adaptive high precision clamping system for flexible bodies: Ein adaptives Spannsystem zur Präzisionsbearbeitung von verformbaren Werkstücken. Issue 4 (May 2015) - Araújo, M.; Janousch, C.; Schwenk, H.; Merkel, M.
Abstract : In manufacturing engineering, especially in machining process, the definition of a reference plane is the first essential step within the overall process. After the reference plane is applied at the component all other features are processed with reference to this basic plane. During any process the component has to be clamped in order to resist the processing forces. There are several clamping systems available, such as pneumatic, magnetic systems or magneto‐rheological (MR) systems. Depending on its stiffness the component is deformed due to the clamping forces, stresses are introduced. This effect can be neglected for components with a high stiffness and nearly rigid body behaviour. However, the deformation of low stiff components under clamping forces, e.g. sheet metals, is relatively large and is in the same range as the addressed accuracy of machining process. Due to the introduced elastic clamping stresses the component will reconfigure after clamping, this phenomenon is known as springback. The focus of this work is the design of a clamping system for flexible bodies in order to reduce the springback and to enable high precision processing. This clamping system consists in a set of supports, which adjust to the surface of the body without introducing stresses and causing no springback after the machining process. The number and the arrangement of the supports are optimized as a function of the intensity and position of the milling force and the geometrical and mechanical properties of the body as well. The functional unit of the clamping system is a cylindrical bodysliding nearly frictionless within a pipe. Numerical simulation is used for configuration and optimization. The developed clamping systems can also be used to process freeform shaped bodies.